PRAKTIK DISKRIMINASI PT GARUDA INDONESIA (PERSERO) TERKAIT PROGRAM WHOLESALER - Alfiyyah Inayah Taqyuddin; Anna Maria Tri Anggraini (Reformasi Hukum Trisakti, 2021)
In March, PT Garuda Indonesia (Persero) issued GA Info which appointed six wholesalers in the distribution of direct sales of Jeddah - Medina umrah tickets and resulted in market barriers for 301 PPIUs to gain access to Garuda Indonesia tickets. The formulation of the problem is; how is the activity or behavior of PT Garuda Indonesia (Persero) in carrying out discriminatory practices resulting in losses to other business actors based on Article 19 letter d of Law Number 5 Year 1999? and whether the considerations of the KPPU Panel in deciding case Number 06/KPPU-L/2020 are in accordance with Law No. 5/1999 and applicable laws and regulations in the field of competition law? Research method is normative, descriptive in nature using secondary data obtained through literature studies and interviews. The data is qualitatively with deductive inference. The results of the research, discussion and conclusions of the author are; that Garuda Indonesia's activities in carrying out discriminatory practices are by appointing six wholesalers, resulting in 301 wholesalers not being able to access airplane tickets directly through Garuda Indonesia and the consideration the KPPU Panel in deciding case Number 06/KPPU-L/2020 is in accordance with Law No. 5/1999 and regulations in field competition law.